Hidden symmetries of the two-particle dirac equation with linear interaction - Tretynyk, V. V (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We investigate Lie and non-Lie symmetries of the two-particle Dirac equation with linear interaction in the one-dimensional case. The integrals of motion and hidden parasupersymmetries are found. By using algebraic method and non-Lie symmetries, we obtain the energy spectra of the considered system